ALL YOU CAN EAT PRACTICE IN MODERN CONSUMER CULTURE: LAW IN ISLAM - Khairi, Muhammad Fakhri; Azzaki , Muhammad Adnan (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The rapid development of the culinary business can be seen from the many modifications and marketing strategies aimed at increasing consumer interest. One of the marketing strategies that has attracted a lot of attention and is increasingly developing in Indonesia is the practice of eating as much as you can or commonly known as "All You Can Eat". The type of research used in this study islibrary research(literature study) with a qualitative approach. The data used in this study are secondary data obtained from various sources such as journals, books, official reports, and other credible and relevant documents. In the practice of eating all you can, consumers can choose and take food from all the menus provided in a buffet style. With just one payment, consumers can take as much food as they want. However, there is a time limit for eating the food that has been taken and if it is not finished, a fine will be given. In this transaction, there is no amount of size, amount and measurement as an object of sale and purchase. Not only that, every human being has a different stomach capacity to accommodate food, so that there will be injustice for consumers. This is also calledevilwhich can be detrimental to one of the parties in a buying and selling transaction. In addition evilin the practice of eating as much as you can also contains usury, such as in the fines given to consumers who do not finish their food. Uncertainty in the contract process will also cause uncertainty in its exchange rate. Thus, some Islamic figures state that buying and selling with the practice of eating as much as you can is valid, this is because the element evilcontained in it aregharar yasiror light so that it can still be forgiven. However, there are also Islamic figures who state that the practice of eating as much as you can is not valid because of the element of usury that comes from fines because consumers do not finish the food that has been provided